Collaborative Governance and Community-Based Sustainable Development in the Neighborhood-Level Fiscal Transfer Program in East Kutai Regency - Budiman; Jumansyah; Qolbi, Yahdi; Patty, Alberto Noviano; Hastira, Muh. Fichriyadi; Burhan, Reksa; Mujiburrahman; Rafdi, Hashfi; Syarifuddin, Tengku Imam; Valmoria, Junsel James Y; Insan, Fakhruddin Jamalul (Jurnal Studi Pemerintahan, 2026)
The Rp250 million per Neighborhood Unit (RT) program in East Kutai Regency represents ultra-micro fiscal decentralization, positioning Neighborhood Units (RTs) as the primary actors in community-based public fund management. This program raises questions regarding the capacity of informal community institutions to implement participatory, accountable, and sustainable development governance. This study employs a mixed-methods approach with a policy evaluation design based on an instrumental case study. Quantitative data were collected through a survey of 400 respondents using proportional cluster sampling across six sub-districts with the highest population density in Kutai Timur Regency. Meanwhile, qualitative data were collected through in-depth interviews, focus group discussions, and field observations, and were analyzed using the interactive model by Miles et al. (2014). The research findings indicate that the program has successfully established a relatively substantive bottom-up participation mechanism. A total of 91.7 percent of respondents stated that activity proposals originated with community members, while 97 percent assessed that funds were used transparently. The program also contributed to improvements in environmental infrastructure, strengthened local economic activities through labor-intensive measures, and increased social capital and community cooperation. However, the program still faces challenges regarding sustainability, particularly concerning weak post-project asset maintenance planning, variations in infrastructure quality due to limited technical capacity at the neighborhood unit (RT) level, and coordination among stakeholders that has not yet been optimally institutionalized. These findings indicate that fiscal decentralization at the community level can strengthen local participation and responsiveness, but still requires institutional capacity building and sustainable governance